Protocol for cell surface biotinylation of magnetic labeled and captured human peripheral blood mononuclear cells - Serife Ayaz-Guner; Mustafa Burak Acar; Dudu Boyvat; Huseyin Guner; Habibe Bozalan; Melis Güzel; Selin Kübra Yıldır; Nilay Altınsoy; Fatma Fındık; Musa Karakükçü; Servet Özcan (STAR Protocols, 2022)
Summary: Analysis of the surfaceome of a blood cell subset requires cell sorting, followed by surface protein enrichment. Here, we present a protocol combining magnetically activated cell sorting (MACS) and surface biotinylation of the target cell subset from human peripheral blood mononuclear cells (PBMCs). We describe the steps for isolating target cells and their in-column surface biotinylation, followed by isolation and mass spectrometry analysis of biotinylated proteins. The protocol enables in-column surface biotinylation of specific cell subsets with minimal membrane disruption. : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.